Theory of Periodic Conjugate Heat Transfer - Zudin, Yuri B. (Mathematical Engineering, 2017)
This book provides a detailed yet comprehensive presentation of the theory of periodic conjugate heat transfer. It contains an analytical approach to the effects of thermophysical and geometrical properties of a solid body on the experimentally determined heat transfer coefficient. The main objective of the book is a simplified description of the interaction between a solid body and a fluid as a boundary value problem of the heat conduction equation. This third and extended edition covers Wall's thermal effect on Landau stability, gas bubbles pulsations in fluids, and also the interplay between periodic conjugate heat transfer and non-Fourier heat conduction. The target audience primarily comprises research experts in the field of thermodynamics and fluid dynamics, but the book may also be beneficial for graduate students in engineering.